Moving Los Angeles Short-Term Policy Options for Improving Transportation - Sorensen, Paul (RAND Corporation, 2008)
Los Angeles has the worst traffic congestion in the country. Excessive traffic congestion detracts from quality of life, is economically wasteful and environmentally damaging, and exacerbates social-justice concerns. The authors of this book recommend strategies for reducing congestion in Los Angeles County that could be implemented and produce significant improvements within about five years.